A Review on The Effect of Corroded Steel Fibre in Fibre Reinforced Concrete - Jamion, Nor Amira Azwa; Ayop, Sallehuddin Shah; Yari, Mohd Asyraf (Recent Trends in Civil Engineering and Built Environment, 2021)
Concrete has a very low tensile strength that contributes to concrete failure. The addition of steel fibers to concrete in a particular percentage has been found to enhance the mechanical properties, durability and serviceability of the structure. Therefore, the objective of this study was to study the effect of corroded steel fibre in fibre reinforced concrete and to determine the capacity between corroded and un-corroded steel fibre in fibre reinforced concrete (FRC). Accelerated corrosion test, compressive strength and corrosion assessment were reviewed in this study based on research conducted by previous researchers. It was found that wetting-drying is the most used method to accelerate corrosion and impressed current can consider a good technique as it consumes the shortest time among the other methods. The review confirms that the capacity of corroded steel fibre lower than un-corroded steel fibre yet the decrement is very small and can negligible. Nevertheless, the corroded fibre gives a negative appearance to SFRC specimens which is the brown spot on the surface of specimens and rust appearance.Through this study, it was revealed that the compressive strength of corroded fibre was slightly reduced compared to un-corroded steel fibre and negligible. However, the corroded steel fibre gave a negative appearance to SFRC specimens.